2008
DOI: 10.1128/mmbr.00038-07
|View full text |Cite
|
Sign up to set email alerts
|

Structural Biology of Pectin Degradation byEnterobacteriaceae

Abstract: SUMMARY Pectin is a structural polysaccharide that is integral for the stability of plant cell walls. During soft rot infection, secreted virulence factors from pectinolytic bacteria such as Erwinia spp. degrade pectin, resulting in characteristic plant cell necrosis and tissue maceration. Catabolism of pectin and its breakdown products by pectinolytic bacteria occurs within distinct cellular environments. This process initiates outside the cell, continues within the periplasmic space, and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
111
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 76 publications
(148 reference statements)
1
111
0
1
Order By: Relevance
“…For both polysaccharides, the typical process is initiated by endoacting polysaccharide lyases (PLs), which cleave the polysaccharide backbone using a β-elimination mechanism, thus producing oligouronates with 4,5-unsaturated nonreducing ends. After being imported into the microbe, these products are completely degraded to 4,5-unsaturated monouronates by oligouronate-specific PLs (1). In pectinolytic organisms, the conversion of 4,5-unsaturated galacturonate (ΔGalUA) to KDG occurs via three steps and the two intermediates 5-keto-4-deoxyuronate (DKI) and 2,5-diketo-3-deoxygluconate (DKII).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For both polysaccharides, the typical process is initiated by endoacting polysaccharide lyases (PLs), which cleave the polysaccharide backbone using a β-elimination mechanism, thus producing oligouronates with 4,5-unsaturated nonreducing ends. After being imported into the microbe, these products are completely degraded to 4,5-unsaturated monouronates by oligouronate-specific PLs (1). In pectinolytic organisms, the conversion of 4,5-unsaturated galacturonate (ΔGalUA) to KDG occurs via three steps and the two intermediates 5-keto-4-deoxyuronate (DKI) and 2,5-diketo-3-deoxygluconate (DKII).…”
mentioning
confidence: 99%
“…Pectin, a complex polyuronate largely made up of the uronate D-galacturonate connected by α-(1,4) linkages, is one such polysaccharide. The principal reservoir of pectin is the primary cell wall of terrestrial plants and, as such, its degradation and metabolism by microbes is an important component of the natural turnover of biomass, infection by plant pathogens, digestion of dietary fiber in the mammalian gut, and the utilization of biomass as feedstocks for biofuels or other valuable products (1). Similarly, alginate, another polyuronate that comprises β-linked D-mannuronate and L-guluronate (in varying lengths and arrangements), is a major cell wall component of brown macroalgae (seaweed).…”
mentioning
confidence: 99%
“…The core pectin polymer consists of alpha-1, 4-linked D-galacturonate subunits, which are then modified by methylation and various oligosaccharide side chains depending on the plant source [1]. Metabolism of galacturonate, which makes up 40% -70% of the dry weight of pectin, has been studied extensively in just a few microbes [2,3]. In this work, we show that the oligotrophic, stalked alpha-Proteobacterium Caulobacter crescentus degrades galacturonate through the hexuronateisomerase pathway, and regulates galacturonate metabolism via LacI-family repressor.…”
Section: Introductionmentioning
confidence: 99%
“…Highly esterified pectin is largely resistant to depolymerization (1). Shevchik and colleagues demonstrated that pretreatment of purified sugar beet pectin with the Erwinia chrysanthemi PMEA resulted in a 10-to 20-fold enhancement in the catalytic rate of E. chrysanthemi pectate lyases PELA, PELB, PELC, PELD, and PELL relative to that of the untreated substrate (21).…”
mentioning
confidence: 99%